Serum neurofilament light is sensitive to active cerebral small vessel disease. (14th November 2017) - Gattringer, Thomas; Pinter, Daniela; Enzinger, Christian; Seifert-Held, Thomas; Kneihsl, Markus; Fandler, Simon; Pichler, Alexander; Barro, Christian; Gröbke, Svenya; Voortman, Margarete; Pirpamer, Lukas; Hofer, Edith; et al.
Abstract : Objective: To explore whether serum neurofilament light chain protein (NfL) levels are increased in patients with MRI-confirmed recent small subcortical infarcts (RSSI) compared to healthy controls and to determine the subsequent course and determinants of NfL levels in a longitudinal manner. Methods: In a prospectively collected group of symptomatic patients with an RSSI (n = 79, mean age 61 ± 11 years, 67% male), we analyzed brain MRI and serum NfL using a Single Molecule Array (Simoa) assay at baseline and at 3 and 15 months after stroke. Community-dwelling healthy age- and sex-matched individuals with comparable severity of MRI white matter hyperintensities (WMH) (n = 53) served as controls. Results: Patients with an RSSI had higher NfL baseline levels compared to controls (73.45 vs 34.59 pg/mL, p < 0.0001), and they were increasingly higher with the time from stroke symptom onset to blood sampling (median 4 days, range 1–11 days, r s = 0.51, p < 0.0001). NfL levels remained increased at the 3-month follow-up but returned to normal at 15 months after stroke. NfL levels were associated with RSSI size and baseline WMH severity and were especially high in patients with new, clinically silent cerebral small vessel disease (CSVD)–related lesions at follow-up. Conclusions: Serum NfL is increased in patients with an RSSI and the occurrence of new CSVD-related MRI lesions, even when clinically silent. This suggests NfL as a blood biomarker for active CSVD.